2013
DOI: 10.1016/j.febslet.2013.03.037
|View full text |Cite
|
Sign up to set email alerts
|

HY5 regulates anthocyanin biosynthesis by inducing the transcriptional activation of the MYB75/PAP1 transcription factor in Arabidopsis

Abstract: Edited by Ulf-Ingo Flügge Keywords:Anthocyanin biosynthesis Arabidopsis HY5 PAP1 a b s t r a c t Several positive transcription factors regulate Arabidopsis anthocyanin biosynthesis. HY5, a component of light-signaling pathways, and PAP1, an R2R3-MYB transcription factor, share common regulatory targets on anthocyanin biosynthesis genes. The epistatic interactions between the two transcription factors are currently unknown. To address this problem, we analyzed crosses between hy5 and pap1 mutants (hy5pap1) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
251
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(265 citation statements)
references
References 23 publications
13
251
0
1
Order By: Relevance
“…Time-lapse imaging revealed that the cotyledons of the hen1-1 mutant opened faster than the Ler wild type (Figure 2A). Light also triggers the accumulation of anthocyanin in wild-type seedlings (Ahmad et al, 1995;Maier et al, 2013;Shin et al, 2013). Light-grown hen1-1 showed high anthocyanin levels ( Figure 2B), which is consistent with hen1-1 being light hypersensitive.…”
Section: Negative Regulatory Roles Of Hen1 In Multiple Aspects Of Skosupporting
confidence: 78%
“…Time-lapse imaging revealed that the cotyledons of the hen1-1 mutant opened faster than the Ler wild type (Figure 2A). Light also triggers the accumulation of anthocyanin in wild-type seedlings (Ahmad et al, 1995;Maier et al, 2013;Shin et al, 2013). Light-grown hen1-1 showed high anthocyanin levels ( Figure 2B), which is consistent with hen1-1 being light hypersensitive.…”
Section: Negative Regulatory Roles Of Hen1 In Multiple Aspects Of Skosupporting
confidence: 78%
“…The transcript of MYB75/PAP1, which encodes a putative MYB domain containing a transcription factor involved in anthocyanin metabolism, was induced by glucose (Table 8). MYB75/PAP1 expression was strongly dependent on HY5, which encodes a component of light-signaling pathways, suggesting that anthocyanin biosynthesis is regulated by HY5 by a bifurcate regulation mechanism (Shin et al, 2013). MYB75/PAP1 can activate other MYB members related to anthocyanin biosynthesis, including PAP2, MYB113, and MYB114 (Shin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…MYB75/PAP1 expression was strongly dependent on HY5, which encodes a component of light-signaling pathways, suggesting that anthocyanin biosynthesis is regulated by HY5 by a bifurcate regulation mechanism (Shin et al, 2013). MYB75/PAP1 can activate other MYB members related to anthocyanin biosynthesis, including PAP2, MYB113, and MYB114 (Shin et al, 2013). The expression of MYB75/PAP1 was positively regulated by sugars (Das et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Following monomerization, UVR8 accumulates in the nucleus and interacts with the positive regulator Constitutively Photomorphogenic 1 (COP1) [139][140][141][142], a WD40/RING-E3 ubiquitin ligase that in non-inductive conditions targets HY5 (Elongated Hypocotyl 5) for proteosome-dependent degradation [143]. HY5 is a key effector of UV-B protection and light photomorphogenic responses [144,145], and it is transcriptionally activated by UV-B in a UVR8-and COP1-dependent manner [146][147][148]. Other components of the UVR8 signalling pathway are repressor of UV-B photomorphogenesis 1 (RUP1) and RUP2.…”
Section: Uvr8-mediated Photomorphogenic Mechanisms In Response To Uv-mentioning
confidence: 99%